The Role of Cash Flow and Accounts Receivable Turnover in Increasing Profitability in A Finance Company - Maria Lusiana Yulianti; Siti Irma Hindriyani; Winna Roswinna (Greenation Research & Yayasan Global Resarch National, 2025)
The purpose of this study is to determine the role of cash turnover and accounts receivable turnover in increasing profitability, both partially and simultaneously, in finance companies registered with the Financial Services Authority. The methods used are descriptive and verificative analysis. The unit of analysis in this study was finance companies registered with the Financial Services Authority, using purposive sampling techniques and obtaining a sample of 14 companies with 70 data samples from company financial reports. The analysis method used was panel data regression with Eviews 13 software. The results of the study indicate that cash turnover fluctuated, accounts receivable turnover increased, and profitability fluctuated in the period from 2020 to 2024. Partially, cash turnover in finance companies registered with the Financial Services Authority plays a role in increasing profitability. Finance companies registered with the Financial Services Authority manage cash effectively and efficiently, so that cash returns to the company faster and better, and is reused for the company's operational activities. Partially, cash turnover plays a dominant role in increasing profitability compared to accounts receivable turnover. However, simultaneously, cash turnover and accounts receivable turnover play a role in increasing profitability in finance companies registered with the financial services authority.